Is There Any Association Between Thrombosis and Tissue Factor Pathway Inhibitor Levels in Patients With Vitamin D Deficiency?. (July 2015) - Topaloglu, Oya; Arslan, Muyesser Sayki; Karakose, Melia; Ucan, Bekir; Ginis, Zeynep; Cakir, Evrim; Akkaymak, Esra Tutal; Sahin, Mustafa; Ozbek, Mustafa; Cakal, Erman; Delibasi, Tuncay
Objective: The aim of this study was to evaluate the relationship between vitamin D levels and hemostatic factors like tissue factor pathway inhibitor (TFPI). Methods: Patients who had 25-hydroxyvitamin D3 (25(OH)D3) levels measured were included. Coagulation and hemostatic parameters were evaluated. Patients were divided into 3 groups based on 25(OH)D3 levels as group 1 (25(OH)D3 < 10 ng/mL, n = 25), group 2 (25(OH)D3 = 10-19.9 ng/mL, n = 22), and group 3 (25(OH)D3 ≥ 20 ng/mL, n = 28). Results: A total of 75 patients with a mean age of 39 (range 18-57) years were included in the study. Prothrombin time was longer in group 3 than in group 2 ( P = .043). The TFPI levels were higher in group 3 than in the other groups ( P < .001). There was a strong positive correlation between 25(OH)D3 and TFPI levels ( r = .47, P < .001). Conclusion: Further studies are needed for evaluation of the role of TFPI in hemostasis and thrombotic process in patients with vitamin D deficiency.